POLA DAN FUNGSI FRASA EKSOSENTRIS DALAM BAHASA INDONESIA - Ririn Sulistyowati (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2023)
Discussions about exocentric phrases in Indonesian are still rare. This statement proven by based on the little discussion in syntax science, both in the form of books and journals which discuss in detail about exocentric phrases in Indonesian. This study will describe in detail the exocentric phrases based on the conjunction elements, both the conjunction elements in the form of prepositions in directive exocentric phrases, and the conjunction elements in the form of articula in non-directive exocentric phrases. This study will also explain the syntactic function of exocentric phrases. This research is a qualitative descriptive study. The data found in the newspapers Media Indonesia, Republika, and Bisnis Indonesia in 2022 were analyzed and concluded by using inductive techniques. Exocentric phrase patterns in Indonesian are P + FN, P + N, P + V, P + P, FP + Pron, P + Pron, P + Num, Adj + P, N + P, P + Adv, Art + N , Art + FN, Art + Adj, and Art + V. Meanwhile, based on its syntactic function, exocentric phrases can occupy syntactic functions as subjects, objects, complements, adverbs, and conjunctions in a sentence in Indonesian.